IDENTIFICATION OF VIBRIO SP. BACTERIAL POPULATIONS IN INTENSIVE VANNAME SHRIMP (LITOPENAEUS VANNAMEI) FARMS AS A PREVENTIVE MEASURE FOR VIBRIOSIS INFECTION - Ramadhani A.W.; Aisyah D.; Ramadhani L.Q.K. (Russian Journal of Agricultural and Socio-Economic Sciences, 2024)
The majority of vannamei shrimp aquaculture activities are carried out intensively with very high stocking densities, leading to a decline in water quality and triggering a series of disease outbreaks. Vibriosis disease outbreaks due to poor aquaculture environmental conditions are characterized by accumulated waste loads. Identification of the causative agents of vibriosis is crucial to ensure disease diagnosis and appropriate therapy as a preventive strategy for vibriosis disease and to maintain production stability. Based on the results of Vibrio sp. bacterial colony counts from 14 observed vannamei shrimp ponds, 6 shrimp ponds still show counts above the maximum threshold of ≥1.0x103 cfu/ml according to the quality standards set by the Ministry of Marine Affairs and Fisheries. However, if the density of Vibrio sp. bacteria reaches 104, it will cause massive shrimp mortality in aquaculture ponds. This is undoubtedly influenced by the water quality of the observed ponds, which remains stable or non-fluctuating and optimal for vannamei shrimp aquaculture activities.